2023
DOI: 10.1186/s13063-023-07103-8
|View full text |Cite
|
Sign up to set email alerts
|

An innovative web-based decision-aid about birth after cesarean for shared decision making in Taiwan: study protocol for a randomized control trial

Abstract: Background Taiwan has a high national caesarean rate coupled with a low vaginal birth after caesarean (VBAC) rate. This study aims to develop and evaluate a web-based decision-aid with communication support tools, to increase shared decision making (SDM) about birth after caesarean. Methods A quantitative approach will be adopted using a randomized pre-test and post-test experimental design in a medical centre in northern Taiwan. The web-based deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…We developed an AI predictive model for VBAC, which was integrated into an innovative DA birth choice platform for SDM. 10 In contrast to conventional DA like booklets, video CDs, pamphlets, or computer-based tools commonly used to aid pregnant women in making birth choices after previous cesarean delivery, 25 29 this platform integrates an AI predictive model. Through this model, women can input seven crucial factors—maternal age, gravidity, BMI, gestational week, history of previous vaginal birth, prolonged labor, gestational diabetes, and pregnancy-induced hypertension—to promptly ascertain their likelihood of achieving a successful VBAC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We developed an AI predictive model for VBAC, which was integrated into an innovative DA birth choice platform for SDM. 10 In contrast to conventional DA like booklets, video CDs, pamphlets, or computer-based tools commonly used to aid pregnant women in making birth choices after previous cesarean delivery, 25 29 this platform integrates an AI predictive model. Through this model, women can input seven crucial factors—maternal age, gravidity, BMI, gestational week, history of previous vaginal birth, prolonged labor, gestational diabetes, and pregnancy-induced hypertension—to promptly ascertain their likelihood of achieving a successful VBAC.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Drawing on previous research findings, 6 – 9 we created an innovative web-based platform serving as the basis for a decision-aid (DA) system for birth choices aimed at fostering shared decision-making (SDM). 10 Through this DA platform, we strive to enhance understanding, boost confidence, and improve communication between medical professionals and pregnant women. The DA platform could be easily operated for pregnant women and healthcare professionals through mobile devices, such as smartphones, tablets, and computers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our systematic review revealed the current format of SDM inter- DAs fall into a different category of access to information because they present information in a way that is tailored to each individual (Chen et al, 2023;Syrowatka et al, 2016). These DAs also enhance understanding in a consistent way by providing systematic feedback to the user as well as using graphical, numerical and textual anchoring formats.…”
Section: Discussionmentioning
confidence: 99%